Cranial structure and condylar asymmetry of adult patients with rheumatoid arthritis - Maria Grazia Piancino; Rossana Rotolo; Rosangela Cannavale; Giovanna Cuomo; Francesco Masini; Paola Dalmasso; Fabrizia D’Apuzzo; Letizia Perillo; Ludovica Nucci (BMC Oral Health, 2023)
Abstract Objective The aim of this prospective cross sectional study was to evaluate the cranial structure and condylar asymmetry of adult patients with rheumatoid arthritis (RA) diagnosed after 25 years of age compared to a healthy adult control group. Methods Eighteen adult patients (57.4 ± 11.4 years) with RA were compared with a control group. Cephalometric analysis and the Habets method for the calculation of the condylar asymmetry were used. The main cephalometric data investigated were focused on the diagnosis of hyperdivergent cranial structure (NSL/ML, NL/ML), backwards rotation of the mandible (Fh/ML), short vertical ramus (Ar:Go), steep mandibular plane (ML/Oc). Results The cephalometric data considered were not significantly different in the RA vs controls except for the steepness of the occlusal plane (NL/Oc), which was steeper in the patients group (P < 0.02) and the ramus of the mandible which was greater in patients. The asymmetry of the condyles was significant (P < 0.003) and different from the control group, but that of the ramus was not. Conclusions In this study, RA patients diagnosed after 25 years of age did not show a different pattern of growth with respect to the control group. As expected, the condyles showed a difference being asymmetrical in RA patients due to the high turnover of this joint reacting to severe systemic inflammation in conditions of continuous functional work, load and forces. This study follows a previous study with the same research plan conducted on young JIA patients who showed a different pattern of growth of the skull leading to a severe hyperdivergent cranial structure with backward rotation of the mandible; this is mainly due to the insufficient growth of the condylar site exposed to the inflammatory process during development. Unlike JIA patients, this study showed that RA patients follow an individual growth pattern not affected by inflammation, even if they show joint asymmetry.